PERAWATAN SISTEM PENDINGIN MESIN DIESEL PADA WHELL LOADER KOMATSU WA120-3CS - NINGRUM ASTRIAWATI; WARIS WIBOWO (LPPM Politeknik LP3I Medan, 2020)
The purpose of this study was to determine how to maintain the cooling system of a diesel engine on the Komatsu WA120-3C Whell Loader. This research was conducted in the Implementation of Public Works Agency Yogyakarta. How to collect data using interviews, observation, and documentation. Data analysis uses descriptive qualitative analysis. The results showed that the maintenance of the cooling system on the diesel engine on the Komatsu WA120-3C Whell Loader had run well and had followed the operational standards contained in the manual book. The maintenance performed on the cooling machine includes water pump maintenance, radiator system maintenance, intercooler maintenance, fan maintenance, radiator hose maintenance, radiator pressure cap maintenance.